2019
DOI: 10.1002/mame.201900155
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Macromolecular Structure and Composition on Mechanical Properties of Films Cast from Solvent‐Free Polyurethane/Acrylic Hybrid Dispersions

Abstract: Polyurethane DispersionPolyurethane (PU) /acrylic dispersions are of great commercial interest due to the synergetic combination of the PU and acrylic polymers. In this work, a series of PU/acrylic dispersions is synthesized by a solvent-free technique and the influence of colloidal structure, grafting between the two polymers, and the nature of the two polymer phases themselves on the mechanical properties of films cast from the dispersions is explored. TEM analysis shows that the particles have a PU shell/ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…By increasing the GMA/AN ratio, polymer films with higher modulus and higher hardness were obtained, but the elongation at break and water uptake decreased. Mehravar et al synthesized a series of hybrids with varying MMA/BA ratios . Again, it was observed that higher quantities of MMA results in higher Young’s modulus and tensile strength but with decreased elongation at break (see Figure ).…”
Section: Structure–property Relationships Of Waterborne Pu/acrylic Hy...mentioning
confidence: 99%
See 3 more Smart Citations
“…By increasing the GMA/AN ratio, polymer films with higher modulus and higher hardness were obtained, but the elongation at break and water uptake decreased. Mehravar et al synthesized a series of hybrids with varying MMA/BA ratios . Again, it was observed that higher quantities of MMA results in higher Young’s modulus and tensile strength but with decreased elongation at break (see Figure ).…”
Section: Structure–property Relationships Of Waterborne Pu/acrylic Hy...mentioning
confidence: 99%
“…Samples grafted are shown with bold lines while nongrafted are shown with dashed lines. Reproduced from ref with permission from John Wiley and Sons.…”
Section: Structure–property Relationships Of Waterborne Pu/acrylic Hy...mentioning
confidence: 99%
See 2 more Smart Citations
“…Here again, the recipes that the models were trained on all had higher hardness values due to their glass transition temperatures being higher, resulting in another bias. In general, hardness has been shown to increase as the glass transition temperature of the polymer increases [72][73] . Varying the glass transition temperature in these batches was needful, as the correlation between the glass transition temperature and the hardness was not established in the network, this correlation can now be learned when the models are retrained with this data.…”
Section: Neural Network Prediction Evaluationmentioning
confidence: 99%